Caracterização molecular de Escherichia coli diarreiogênica Durante a SHELF LIFE e maturação a vácuo de Longissimus lumborum - Meurer, Carolina Merlin (Universidade Federal do Tocantins, 2023)
Over the past decade, Brazil assured its position as the second-largest producer of bovine beef in the global market. In addition, according to the Ministry of Agriculture, Livestock and Food Supply and Brazilian Agricultural Research Corporation projection, in the next ten years the beef consumption will increase by 10,4%. To accompany production growth, it is also necessary to increase its physical, chemical and microbiological quality. The enterobacteria Escherichia coli is suggestive of an indication of faecal contamination origin, regarding a meat indicator of inadequate processing during slaughter. It is important for public health once some strains are associated with cases of diarrhea in epidemiological studies. The objective of the present work was to determine the count and molecular characterization of diarrheagenic E. coli during the vacuum-packed sirloin (Longissimus lumborum) shelflife. Five cutting parts were acquired in a slaughterhouse of federal inspection and analyzed on days 0, 20, 40 e 60 after vacuum-packed. Counting and identification of E. coli were performed using official methods. Multiplex PCR assays submitted isolates for gene identification that encodes virulence factors that characterize diarrheagenic E. coli: enteropathogenic (EPEC), enteroaggregative (EAEC), enterotoxigenic (ETEC), enteroinvasive (EIEC), Shiga toxin-producing (STEC) and enterohemorrhagic (EHEC). It was verified the incompatibility of E. coli counting in accordance with the Brazilian Health Regulatory Agency standard envisioned of 100 UFC/g from day 20 and microbial growth lower than expected on day 60. Regarding isolates molecular characterization, stx2 and ipaH genes predominated during the analyses. On day 20, isolates were identified with genes that encode virulence factors for EPEC, ETEC, STEC and EIEC, on day 40 for EPEC and on day 60 for STEC and EIEC, highlighting the importance of sanitary measures adoption in order to reduce infection and intoxication cases related to pathogenic E. coli to consumers.